2019
DOI: 10.9734/ajee/2019/v9i130084
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Smallholder Farmers’ Perceptions on Climate Change, Preference and Willingness-to-pay for Seasonal Climate Forecasts Information in Savelugu Municipality, Ghana

Abstract: Aim: Agricultural production is directly affected by climate change. This means that access to climate information would help the farmers’ preparedness for farming activities and the decision on the types of crops to grow, when to grow them and the types of farm management activities to adopt. As such, this study analysed farmers’ preference for seasonal climate forecasts and their willingness-to-pay for these information. Place and Duration: The study was conducted in the Savelugu Municipality in the No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In exploring the urgency of the customary values and traditions in farm management systems among smallholder farmers in Indonesia [ 60 ],observed that indigenous knowledge and practices are deployed at various stages of farming, from identification of farm site through to harvesting and performance of traditional thanksgiving services [ 61 ].also found that the contributions of indigenous pastoralists to household income through livelihood diversification were significantly influenced by their access to credit, market, age of household head, use of farm inputs, frequency of extension contacts, market access, and ownership of assets. In Burkina Faso [ 38 ], found that the ability or inability of smallholder farmers to pay for improved climate services were determined by their socio-demographic characteristics such as the level of education, age, gender, and level of awareness on climate information [ 20 ]. also observed that smallholder farmers’ production decisions are influenced by their level of access and participation in government subsidies and related programmes, perceptions and experience about improved production services, access to alternative livelihood activities and source of agricultural information.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In exploring the urgency of the customary values and traditions in farm management systems among smallholder farmers in Indonesia [ 60 ],observed that indigenous knowledge and practices are deployed at various stages of farming, from identification of farm site through to harvesting and performance of traditional thanksgiving services [ 61 ].also found that the contributions of indigenous pastoralists to household income through livelihood diversification were significantly influenced by their access to credit, market, age of household head, use of farm inputs, frequency of extension contacts, market access, and ownership of assets. In Burkina Faso [ 38 ], found that the ability or inability of smallholder farmers to pay for improved climate services were determined by their socio-demographic characteristics such as the level of education, age, gender, and level of awareness on climate information [ 20 ]. also observed that smallholder farmers’ production decisions are influenced by their level of access and participation in government subsidies and related programmes, perceptions and experience about improved production services, access to alternative livelihood activities and source of agricultural information.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many of these interventions target at promoting CSA practices and technologies such as irrigation, use of improved seeds and other inputs, provision of extension services, and agroforestry among smallholder farmers. For instance, the Government of Ghana, civil society organisations, and donor organisations have adduced policy interventions such as the provision of small-scale irrigation dams, supply of agriculture inputs and farm equipment, including training farmers on improved farming methods to enhance the adaptive capacities of farmers for food production [ 4 , 20 , 21 ]. These interventions seek to promote agricultural practices that are not only climate-smart but also climate compatible and can enhance food crop production and food security under climate change.…”
Section: Introductionmentioning
confidence: 99%